Culturable endophytic fungal diversity in cassava tubers of Indonesia - Anastasia Tatik Hartanti; Felicia Nike Susanti; VIVITRI DEWI PRASASTY; Nani Radiastuti (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hartanti AT, Susanti FN, Prasasty VD, Radiastuti N. 2021. Culturable endophytic fungal diversity in cassava tubers of Indonesia. Biodiversitas 22: 1250-1260. Fungal endophytes are found in plant tissue and do not harm the host plant. Cassava (Manihot esculenta Crantz) is the third staple food besides rice and corn. This study aimed to identify the diversity of endophytic fungi in the cassava from several regions in Indonesia, including Bogor, Lembang, Makasar, Serang, Singaraja (Buleleng), Subang, Wonogiri, and Wonosobo. The endophytic fungi were isolated and were molecularly characterized using the internal transcribed spacer (ITS) rDNA sequence (ITS4 and ITS5). Phylogenetic analysis was performed by using the MEGA 7 with a bootstrap value of 1000 repetitions. All 14 isolates of endophytic fungi were isolated from different regions. Of these six isolates belonged to genus Fusarium (F. solani FS5, F. lichenicola FS2, F. lichenicola FS4, F oxysporum FS1, F. falciforme FS3, F. falciforme FS6), and four to the genus Aspergillus (Aspergillus sp. FS7, Aspergillus sp. FS8, Aspergillus sp. FS9 and A. fumigatus FS10). In addition, Nectria pseudotrichia, Lasiodiplodia sp., Penicillium citrinum, and Schizophyllum commune were also isolated from cassava tubers. In conclusion, it suggested that diverse endophytic fungi colonize tubers of cassava growing in Indonesia.